Critical Values of Facet Joint Angulation and Tropism in the Development of Lumbar Degenerative Spondylolisthesis: An International, Large-Scale Multicenter Study by the AOSpine Asia Pacific Research Collaboration Consortium. (August 2016) - Samartzis, Dino; Cheung, Jason Pui Yin; Rajasekaran, Shanmuganathan; Kawaguchi, Yoshiharu; Acharya, Shankar; Kawakami, Mamoru; Satoh, Shigenobu; Chen, Wen-Jer; Park, Chun-Kun; Lee, Chong-Suh; Foocharoen, Thanit; Nagashima, Hideki; et al.
Study Design: An international, multicenter cross-sectional image-based study performed in 33 institutions in the Asia Pacific region. Objective: The study addressed the role of facet joint angulation and tropism in relation to L4–L5 degenerative spondylolisthesis (DS). Methods: The study included 349 patients (63% females; mean age: 61.8 years) with single-level DS; 82 had no L4–L5 DS (group A) and 267 had L4–L5 DS (group B). Axial computed tomography and magnetic resonance imaging were utilized to assess facet joint angulations and tropism (i.e., asymmetry between facet joint angulations) between groups. Results: There was a statistically significant difference between group A (left mean: 46.1 degrees; right mean: 48.2 degrees) and group B (left mean: 55.4 degrees; right mean: 57.5 degrees) in relation to bilateral L4–L5 facet joint angulations ( p  < 0.001). The mean bilateral angulation difference was 7.4 and 9.6 degrees in groups A and B, respectively ( p  = 0.025). A critical value of 58 degrees or greater significantly increased the likelihood of DS if unilateral (adjusted OR: 2.5; 95% CI: 1.2 to 5.5; p  = 0.021) or bilateral facets (adjusted OR: 5.9; 95% CI: 2.7 to 13.2; p  < 0.001) were involved. Facet joint tropism was found to be relevant between 16 and 24 degrees angulation difference (adjusted OR: 5.6; 95% CI: 1.2 to 26.1; p  = 0.027). Conclusions: In one of the largest studies assessing facet joint orientation in patients with DS, greater sagittal facet joint angulation was associated with L4-L5 DS, with a critical value of 58 degrees or greater increasing the likelihood of the condition for unilateral and bilateral facet joint involvement. Specific facet joint tropism categories were noted to be associated with DS.